Effects of Reading Strategy and Dictionary Instruction in an Undergraduate Foreign Language Reading Comprehension Group (2019)
ABSTRACT: This article reports the effects of the integration of dictionary use and the reading strategy approach in a foreign language reading comprehension course. A case study was used as a research method, and three instruments helped gather data: a reading comprehension test, field notes, and an interview. Fifteen undergraduate students from a public university in Medellin, Colombia, participated in the study. Improvement in reading, metacognitive awareness, and selective use of dictionary were found as part of positive effects. In contrast, tiredness appears to be as the negative effect. Conclusions suggest that both the reading strategy approach and the selective use of dictionary are a good combination to integrate into a foreign language reading course.